Criminal Liability for Perpetrators of Election Crimes Who Vote More Than Once at a Polling Station - Majid Ansar; Aswad Karimali; La Yopi; M. Gafur; Muhammad Aksan (AIQU: Journal Multidiscipliner of Science, 2025)
This study aims to analyze how election crimes are handled and how criminal sanctions are applied within the electoral process, given that election-related offenses remain a recurring problem that can undermine electoral integrity and public trust. Effective handling and sanctioning require a regulatory framework that not only defines prohibited conduct, but also ensures legal certainty, proportionality, and justice for all parties involved. The research focuses on the normative structure of regulations and sanctions governing election crimes. It employs normative legal research methods by examining primary legal materials especially statutory provisions and codified criminal norms as well as secondary legal sources such as scholarly literature and legal commentaries. The analysis shows that election crimes are addressed in general criminal law through Chapter IV, Book II of the Criminal Code, while the electoral framework is specifically regulated under Law Number 7 of 2017 on Elections. In this context, election crimes constitute a special category of offenses because elections are conducted through a sequence of strictly regulated stages, making the timing, actors, and procedural requirements more determinative than in ordinary crimes. Furthermore, criminal sanctions are explicitly enumerated in the Election Law, particularly Articles 488 to 544, which provide various forms and levels of punishment. The imposition of sanctions is determined by the legal qualification of the act committed, reflecting the gravity, intent, and impact of the offense on the electoral process.